NUMERICAL INVESTIGATION OF THE DYNAMIC SOIL-STRUCTURE INTERACTION OF CONCRETE BUILDINGS - Al-Tameemi, Zain Aldin; Naimi, Sepanta; Mubarak, Loay (Journal of Applied Engineering Science, 2023)
This research is carried out to investigate and assess the dynamic soil-structure interaction features related to a reinforced concrete building. Numerical analysis and mathematical simulations were performed depending on the ABAQUS® software package to achieve the study goal. Structures with floor numbers ranging between one and ten were modelled and simulated, and soil characteristics were explored and measured in terms of base shear, axial force, moment, and displacement, taking into account dynamic soil-structure interaction principles. In addition, the effect of soil type on the building stability and soil performance was assessed and examined. The research findings revealed that the base shear for a five-floor building frame decreases by 5% from soft to medium soil and by 23% from medium to hard soil. Also, the base shear for a five-floor building frame reduces by 5% from soft to medium soil and by 23% from medium to hard soil. The base shear for a shear wall system with ten stories on medium soil is 20% less than that on soft soil. On hard soil, this outcome is lowered by 12%. The axial force for a five-floor building frame decreases by 2% from mild to medium soil and by 8% from medium to hard soil. Additionally, axial forces provide a 9% decrease for medium soil and a 4% reduction for hard soil in a 10-floor building frame resistance system. There is a reduction of 3% from soft to medium soil and a reduction of 12% on hard soil regarding axial force. Meantime, the axial forces are lesser for medium soil by 13% compared to soft soil and less by 6 % for hard soil. The displacement is decreased by 6% in a 5-floor building frame system on medium soil and 11% on hard soil. However, the displacement of a 10-floor building structure is reduced by 10% on medium soil and 22% on hard soil. Displacement in a five-floor shear wall structure is decreased by 6% and 18% on medium and hard soil. Also, displacement reduces by 20% and 30% on medium and hard soil, respectively.
Keywords: soil type, simulations, base shear, axial force, moment